1997
DOI: 10.1046/j.1365-2516.1997.00105.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of recombinant factor VIIa in surgery in factor‐VII‐deficient patients

Abstract: Patients suffering from severe factor VII deficiency may present with serious bleeding problems. No clear guidelines exist regarding therapy in such patients in case of a large bleeding or surgery. Indeed, it has been postulated that some patients with severe factor VII deficiency may never present with overt bleeding problems. However, in factor-VII-deficient patients who have previously demonstrated a clinical tendency to bleed, surgery is expected to cause excessive bleeding. We present two females sufferin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
1
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(53 citation statements)
references
References 5 publications
1
50
1
1
Order By: Relevance
“…As the presence of rVIIa is thought to be required when haemostasis is challenged, prophylaxis with rVIIa would seem unlikely to succeed because of its short half-life in blood. On-demand therapy with rVIIa for FVII deficiency has been described before in small studies and case reports (Bauer, 1996;Ingerslev et al, 1997;Mariani et al, 1999;Hunault & Bauer, 2000;Berrettini et al, 2001;Charpiat et al, 2002;Eskandari et al, 2002). Furthermore, rVIIa has been administered for many indications, such as haemophilia A and B with inhibitors, for which the product was originally developed, surgical procedures or trauma in otherwise healthy patients (Hedner, 2003).…”
Section: Patient 1 Patient 2 Patientmentioning
confidence: 97%
“…As the presence of rVIIa is thought to be required when haemostasis is challenged, prophylaxis with rVIIa would seem unlikely to succeed because of its short half-life in blood. On-demand therapy with rVIIa for FVII deficiency has been described before in small studies and case reports (Bauer, 1996;Ingerslev et al, 1997;Mariani et al, 1999;Hunault & Bauer, 2000;Berrettini et al, 2001;Charpiat et al, 2002;Eskandari et al, 2002). Furthermore, rVIIa has been administered for many indications, such as haemophilia A and B with inhibitors, for which the product was originally developed, surgical procedures or trauma in otherwise healthy patients (Hedner, 2003).…”
Section: Patient 1 Patient 2 Patientmentioning
confidence: 97%
“…Mean dose/procedure ranged from 13.85 to 26.29 μg/kg and the number of doses/procedure varied from 30 to 112. Other results from different groups showed that 20 -25 μg/dL of rFVII should be given at every 4 -6 h in combination with tranexamic acid which was seen to be effective in surgical settings for FVIId patients but treatment duration is not well defined [5,8,9,15]. Pharmacokinetic studies of rFVII helped in choosing the dose and time interval between the subsequent infusions, but it is still not defined about minimum requirement for FVII in plasma to attain hemostasis [15,16].…”
Section: Discussionmentioning
confidence: 99%
“…According to UK guidelines, the management of rare bleeding disorder in patients with FVIId undergoing surgery requires plasma level of 20 IU/ dL with FVII plasma derived concentrate [5]. Ingerslev et al [15] in his study of two patients diagnosed with severe FVIId, showed rFVII cover was used for homeostasis and concentration of FVII was kept at 30 IU/dL. Al Dieri et al [17] had a contrasting result as he postulated that 2 IU/dL concentration of FVII is sufficient for normal thrombin generation but the drawback is it was an observation in one patient who had a normal thrombin potential value.…”
Section: Discussionmentioning
confidence: 99%
“…The time interval until the next bolus can be prolonged during the course of treatment, depending on the bleeding pathology. In many instances a subsequent injection regime of twice a day is sufficient [41,62].…”
Section: Bleeding and Prevention Of Bleeding In Patients Withmentioning
confidence: 99%